PENGARUH PENGELUARAN PER KAPITA DAN BELANJA KESEHATAN TERHADAP ANGKA KESAKITAN DI KABUPATEN/KOTA SE-PULAU JAWA. - Amru, Dania Setira; Sihaloho, Estro Dariatno (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
This paper focuses on two objectives. First, this paper estimates the effect of expenditure per capita on mordibity rate in regencies and cities in Java Island. Second, this paper estimates the effect of health expenditure or health budget allocation on mordibity rate in regencies and cities in Java Island. Mordibity rate is a percentage of people who is sick in some area at a certain period of time. This paper uses a Cross Section Data OLS. This paper uses cross section data of 113 Regencies and Cities in Java Island from 2018. This paper use mordibity rate as the dependent variable, expenditure per capita and health budget allocation as the independent variable. The result of this paper shows that Cross Section Data OLS estimate expenditure per capita has a negative and significant effect on mordibity effect. Cross section data OLS estimate health budget allocation has a negatve and not significant effect on mordibity rate in regencies and cities in Java Island.